ความร่วมมือระหว่างรัฐในระบอบการจัดการแม่น้ำระหว่างประเทศ : ศึกษาเปรียบเทียบกรณีแม่น้ำยูเฟรตีส-ไทกริสและแม่น้ำโขง - วีระพงษ์ ปัญญาธนคุณ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This thesis is a qualitative research which aims to compare the effectiveness of two international river regimes, namely, the Mekong regime under Mekong Committee and Mekong River Commission (1957-2008) and the Euphrates-Tigris regime under Joint Technical Committee (1980-1993), and to provide an analysis on the factors influencing the levels of effectiveness of both regimes. The findings of the study are as follows. 1) In reference to Arild Underdal’s approach concerning the evaluation targets of the effectiveness of environmental management regimes, the effectiveness of the Euphrates-Tigris regime is much lower than that of the Mekong regime. The Euphrates-Tigris regime is evaluated as "successful at a low level" because of its inability to generate either the output or the outcome resulting from the implementation and compliance of mutual agreement. However the regime caused a positive side effect involving information exchange between the riparian member-states. The Mekong regime, on the other hand, is evaluated as "partially successful" on account of its ability to bring about many outputs. The implementations of these outputs were, however, limited in scopes and aspects, including especially the implementations on hydrological and technical research, and the adherence of member-states to institutional rules and regulations; whereas water-use rules caused no apparent change on member-states’ behaviors. As a positive side effect, the Mekong regime was also able to convince China to suspend further operations of improvement projects for commercial navigation on the upper Mekong river. 2) By categorizing the factors influencing the regime effectiveness into five groups, in accordance with Stefan Lindemann’s approach, namely:- problem factors, process factors, institutional factors, country-specific factors and factors of International context, this study finds that the Euphrates-Tigris regime was less effective because it was confronted with more negative factors than the Mekong regime. The Euphrates-Tigris regime had to deal with almost all the five negative factors. In contrast, The Mekong was involved with both positive factors and with less serious negative factors than the Euphrates-Tigris regime. In addition, the higher level of effectiveness of the Mekong regime was significantly caused by the support and assistance of external actors